PENGARUH PROGRAM EKSTENSIFIKASI DAN INTENSIFIKASI PAJAK, NPWP SERTA SUNSET POLICY TERHADAP PEMENUHAN KEWAJIBAN PERPAJAKAN - Amaliyah, Mistaul; Murtin, Alex (Universitas Muhammadiyah Yogyakarta, Indonesia, 2010)
This research was conducted to see how perceptions tax extensification and intensification programe, tax identification number (NPWP), with sunset policy to tax compliance to the respondent an individual tax payer and the entity that reported as many as 250 tax on each KPP Pratama Yogyakarta, Sleman, wonosari, Wates, and Bantul taken by simple random sampling method. Data analysis using an analytical approach to structural equation models (SEM) software using partial least square (PLS). Test results that the perception of tax extensification and intensification programe, NPWP with facility sunset policy that has been applied by the Directorate General of Taxes has not impacted significantly to tax compliance with t-statistic value of each (0.70, 0098, 0.436) t-table (1.645). Test results that the perception of tax extensification and intensification programe has been implemented by the Directorate General of taxes can have a positive impact on facility sunset policy with t-statistics value of each of (1.742, 2.211) t-table (1.645). Test results that with the addition of NPWP provided by the Directorate General of Taxes can have a positive impact on tax compliance to the value of t-statistic (2.313) t-table (1.645). The perception of tax extensification programe and facilities sunset policy that have been implemented by the Directorate General of Taxes can have a positive impact on the addition NPWP with t-statistics value of each of (1.929, 2.626) t-table (1.645). The programs and facilities as well as NPWP implemented by Directorate General of Taxes should be increased and expanded again to the awareness of taxpayers in tax compliance to boost significantly impact (voluntary compliance)